Ferroptosis: new insight into the mechanisms of diabetic nephropathy and retinopathy - Li, Luxin; Dai, Yucen; Ke, Dan; Liu, Jieting; Chen, Peijian; Wei, Dong; Wang, Tongtong; Teng, Yanjie; Yuan, Xiaohuan; Zhang, Zhen (Frontiers in Endocrinology, 2023)
Diabetic nephropathy (DN) and diabetic retinopathy (DR) are the most serious and common diabetesassociated complications. DN and DR are all highly prevalent and dangerous global diseases, but the underlying mechanism remains to be elucidated. Ferroptosis, a relatively recently described type of cell death, has been confirmed to be involved in the occurrence and development of various diabetic complications. The disturbance of cellular iron metabolism directly triggers ferroptosis, and abnormal iron metabolism is closely related to diabetes. However, the molecular mechanism underlying the role of ferroptosis in DN and DR is still unclear, and needs further study. In this review article, we summarize and evaluate the mechanism of ferroptosis and its role and progress in DN and DR, it provides new ideas for the diagnosis and treatment of DN and DR.